Unlocking the Public-Private Partnerships Deadlock in Indonesia - Wibisono, Andri; Delmon, Jeff; Hahm, Hongjoo (World Bank, Jakarta, 2017)
The challenges faced by Indonesia in creating a robust Public-Private Partnership (PPP) program are similar to those faced by many other middle-income countries. This paper provides a gap analysis for Indonesia's PPP framework based on lessons learned and good practice from countries with successful PPP programs. It identifies, in particular, the need for the government to: select good projects for PPP, rather than only complex ones that are less likely to attract private partners. Establish a list of projects by a limited cabinet meeting and stick to it-issuing different lists of projects and holding showcase summits with open agendas tends to confuse the market. Keep those projects on track for PPP-allowing the contracting agencies to develop prospective projects directly, or to award them without competition leads investors to question the commitment and resolve of the government to its own PPP process. Prepare projects well, using the Ministry of Finance to provide access to: 1) a team of PPP experts to help contracting agencies develop projects; 2) project preparation funding to help pay the high costs of preparation; and 3) viability gap funding to make projects more affordable and bankable by defraying some of the capital costs.